Should mothers provision their offspring equally? A manipulative field test. (19th July 2017) - Cameron, Hayley; Monro, Keyne; Marshall, Dustin J.
Abstract: Within‐brood variation in offspring size is universal, but its causes are unclear. Theoretical explanations for within‐brood variation commonly invoke bet‐hedging, although alternatives consider the role of sibling competition. Despite abundant theory, empirical manipulations of within‐brood variation in offspring size are rare. Using a field experiment, we investigate the consequences of unequal maternal provisioning for both maternal and offspring fitness in a marine invertebrate. We create experimental broods of siblings with identical mean, but different variance, in offspring size, and different sibling densities. Overall, more‐variable broods had higher mean performance than less‐variable broods, suggesting benefits of unequal provisioning that arise independently of bet‐hedging. Complementarity effects drove these benefits, apparently because offspring‐size variation promotes resource partitioning. We suggest that when siblings compete for the same resources, and offspring size affects niche usage, the production of more‐variable broods can provide greater fitness returns given the same maternal investment; a process unanticipated by the current theory.